Robotic PCI: Evolving from novel toward non‐inferior. Issue 4 (12th March 2019) - Cheney, Amy E.; Dean, Larry S.
Key Points: Robotic‐assisted PCI appears to be safe and feasible in both simple and complex lesions. In this small cohort study, analysis of manual versus robotic PCI suggests comparable clinical outcomes. Further adequately powered, randomized, multicenter studies are needed to definitively evaluate outcomes in manual versus robotic‐assisted PCI.